Evaluation of scanner parameters on ebt 2 And ebt 3 film analysis - Azhan, Siti Nur Amirah (Universiti Sains Malaysia, 2016)
This study investigates the effects of scanner parameters properties to EBT 2 and EBT 3 films analysis irriadiation with photon and electron beam energy. The scanner parameters evaluated are interpretation (no invert, invert 8-bit scan, invert 16-bit scan), colour to grayscale transformation (Gafchromic optimised and user-defined transformation), flattening correction (no filter and median filter), film type (positive and colour negative film), image type (bit colour and grayscale), and resolution (72 dpi, 300 dpi, 600 dpi). The EBT 2 and EBT 3 films were initially irradiated with photon and electron beams of different energies (6 MV, 10 MV, 6 MeV and 9 MeV) using Siemens Primus Linear Accelerator. After irriadiation, the films were then scanned using Epson Expression 10000 XL flatbed using different scanning parameters. As a result, the scanner flattening correction did not have any effects the optical density (OD) reading of EBT 2 and EBT 3 films. However, the interpretation section of scanner parameter did changes if invert 16-bit scan was used compared to similar reading obtained if invert 8- bit scan and standard parameter (no invert) were used. The OD of film type is significantly different than the standard parameter and the image type also affect the OD value. The different parameter of resolution flatbed scanner gives almost consistent OD value but changes to the higher resolution will increase the OD value. In conclusion, the scanning parameters have significant effects on the films OD analysis and hence affect the dose measured.